Internationalization of education as an emerging field? A framing of international education for cross-domain analyses. Issue 6 (September 2019) - Tarc, Paul
The internationalization of education (IE) has accelerated across the past two decades. Although there are now a range of representations and theorizations of IE, they find little connection across domains and levels. Toward bolstering a more coherent field of IE, which translates across distinctive expressions of IE, this paper argues for a conceptual approach that includes theorizing IE's past and present enabling conditions, motivating visions, significant (operational) obstacles, and ensuing tensions. The main contribution is a conceptualization of late 20th century international education, which historically situates the current 21st century IE movement. This conceptualization is informed primarily by a periodization of the International Baccalaureate that surfaces the semantic contours and structuring tensions of international education as embedded in the shifting historical and socio-political conditions of the last 50 years. Semantically, 20th century international education carries with it literal (educational activities across national jurisdictions) and normative/aspirational significations (liberal-humanist education for making a better world). And the structuring tensions of international education are constituted in the entangling of the normative visions, as "education for international understanding, " with the instrumental agendas, as revenue generation. An emerging IE field can draw on the conceptual framing offered in this paper as a basis for theorizing across the somewhat siloed IE discourses.